The Evolution of Muhammadiyah in Banda Aceh Throughout The Period of 19231943 - Alfian*, Alfian; Haikal, Muhammad (Universitas Syiah Kuala, 2023)
The purpose of research on the development of Muhammadiyah in Banda Aceh (19231943) is to explain the journey of Muhammadiyah, starting from its entry and development in Acehnese society and culture before independence, as well as the role and contribution of Muhammadiyah in the development of Acehnese society both in the religious, educational, political, and social fields. The methods used in compiling this thesis are historical methods, namely: heuristics, source criticism, interpretation, and histiography. In heuristics, sources about the development of Muhammadiyah in Aceh are obtained by collecting written sources. Source criticism is used so that the validity of the data can be assessed for its objectivity through internal and external criticism. The interpretation method is used to ensure the results of the study by comparing them with previous research. Histography is the preparation of research results into descriptive historical papers and analyses. The idea of Muhammadiyah itself had emerged in Aceh in 1923, and it was originally introduced by a Dutch pawnshop employee from Sunda, the late Djajasoekarta. But according to records, the Muhammadiyah organization was only officially established in Banda Aceh in 1927 and then only expanded to the east coast and other Aceh regions. This movement also began to implement the teachings of Islam in a modern way by establishing schools and other educational institutions. Muhammadiyah in Aceh also took part in the political field, in addition to the social field of helping the poor and orphans obtain proper education in Aceh and Banda Aceh in particular. Besides its main mission, it is to purify the teachings of Islam in accordance with the Quran and Hadits